Early Impact of COVID-19 on Solid Organ Transplantation in the United States. Issue 11 (November 2020) - Cholankeril, George; Podboy, Alexander; Alshuwaykh, Omar S.; Kim, Donghee; Kanwal, Fasiha; Esquivel, Carlos O.; Ahmed, Aijaz
Abstract : Background: The regional impact of coronavirus disease 2019 on solid organ transplantation in the United States has not been fully evaluated. Methods: A retrospective analysis of month-to-month trends on waitlist additions, waitlist deaths, and transplant surgeries between all United Network for Organ Sharing (UNOS) regions was performed. A linear regression model trained on historical data was used to estimate anticipated transplantation volume. Results: All UNOS regions reported a decrease in total waitlist additions and transplant surgeries. The largest decreases in total transplants were identified in regions 1, 2, 6, and 9, with regions 2, 7, 8, and 9 noting the largest decrease in waitlist additions. Six of the 11 regions noted increases in waitlist deaths, with UNOS regions 9, 1, and 2, all located within the Northeast, noting the highest percent increase in waitlist deaths at 170%, 89%, and 54%, respectively. The largest reductions in solid organ transplantation and waitlist deaths were seen in kidney and lung transplantation. Current transplantation volume is significantly lower than the low range of the 95% confidence interval derived from the linear regression model (2182 versus 3110; P  < 0.05). Conclusions: Significant decreases in total waitlist additions and transplant surgeries with increases in waitlist deaths were noted in the majority of US transplant domains. The impact was especially prevalent in areas with high burden of coronavirus disease 2019 infection. National and regional strategies aimed at minimizing disruptions in transplantation are needed. Abstract : Supplemental Digital Content is available in the text.